Listening and Speaking Pedagogical Approaches towards the Development of Innovative Macro Skills among English Teachers in Binakayan National High School: A Narrative Study - Estavillo, Shiela E. (Educalingua Journal, 2024)
A child becomes able to speak after getting enough exposure to the language through listening. This only proves that listening and speaking are the most important skills to be developed first among all skills. But, despite this truth of importance, for many years, these two skills do not receive any priority in language teaching and testing. Hence, this study aims to analyze the listening and speaking pedagogical approaches of Binakayan National High School English teachers, their impact to their profession as language teachers through their response to the challenges, and their contribution for the development of innovative macro skills. This research is a narrative study using a purposive sampling with pre-set criteria for the prospect respondents. Data gathering was done through interviews, self-made questionnaires which underwent content validation, and focus group discussion as research instruments. In data analysis, transcribing/inductive coding and thematic analysis were utilized in getting the emerging ideas of the study. The study ‘s findings and results state that Binakayan National High School English teachers apply listening and speaking pedagogical approaches in their instructional plan through task-based and interactive teaching and learning approaches, they respond to challenges of these approaches gracefully which lead them become more dedicated to their profession as language teachers, and enumerating the pedagogical approaches they apply in their English classroom, still they need more technical assistance on the development of strategies and techniques towards innovative macro skills.